Blue bits : archives of the average hour - Tan, Jeremy Jie Ming (2016)
Blue Bits: Archives of the Average Hour is a personal attempt at objective mundane-moment documentation. I have archived the end of a year alongside four individuals with whom I interact regularly. The final outcome is a visual archive housed within an exhibition space, therein also containing a collection of design objects that comprise illustrations, print material, and found ephemera that serve to accentuate the concept of the project, encapsulating the objective archival of an eventful uneventful November to December 2015.